Criminal Law Protection of the Environment in the European Union - Batrićević, Ana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Over the past several decades, a growing concern for environmental problems among experts, stakeholders, law and public policy-makers, as well as the general public, has encouraged the development of a large and comprehensive legislative framework at the level of the European Union, regulating various ecological issues in the European Union. The risks of environmental pollution and the awareness of the need to provide for efficient, adequate and universal protection of the environment in all European Union member states have led to the adoption of Directive 2008/99/EC on the protection of the environment through criminal law (Official Journal of the European Union, No. 328, 6.12.2008). The aim of this paper is to analyse the key provisions of this legal instrument, the means of its implementation in national legislations, as well as the mechanisms for its effective application. Moreover, the conditions that have to be met in order to facilitate the successful transposition of this Directive's provisions through the alterations of the Criminal Code of the Republic of Serbia are also analysed.